Mystic river - Eastwood, Clint, 1930-; Hoyt, Judie; Lorenz, Robert; Helgeland, Brian; Penn, Sean, 1960-; Robbins, Tim, 1958-; Bacon, Kevin, 1958-; Fishburne, Larry; Harden, Marcia Gay.; Linney, Laura; Chapman, Kevin; Nelson, Adam.; et al. (Burbank, CA : Warner Home Video, 2004)
Boston childhood friends Jimmy, Sean, and Dave are reunited after a brutal murder. Reformed convict Jimmy and his devoted wife Annabeth find out that their teenage daughter Katie has been beaten and killed. Jimmy's old friend Sean is the homicide detective assigned to the case. Jimmy gets his in-laws, the Savage brothers, to conduct their own investigation. Jimmy and Sean soon suspect their old pal Dave, who now lives a quiet life, but harbors some disturbing secrets of his own.
DVD, Region 1, widescreen (2.40:1) presentation; Dolby Digital 5.1 surround.
English or dubbed French dialogue, French or Spanish subtitles; closed-captioned.
Sean Penn, Tim Robbins, Kevin Bacon, Laurence Fishburne, Marcia Gay Harden, Laura Linney, Kevin Chapman, Adam Nelson, Tom Guiry.
Director of photography, Tom Stern ; editor, Joel Cox ; original music, Clint Eastwood ; costume designer, Deborah Hopper ; production designer, Henry Bumstead ; visual effects supervisor, Mark Freund.
Originally released as a motion picture in 2003.
Based on the novel by Dennis Lehane.
Keywords: Murder -- Investigation -- Massachusetts -- Boston -- Drama; Friendship -- Massachusetts -- Boston -- Drama; Detectives -- Massachusetts -- Boston -- Drama